SAT0235 BIIB059, a monoclonal antibody targeting BCDA2 shows safety, tolerability, pharmacokinetics, pharmacodynamics in healthy volunteer subjects. (15th June 2017) - Martin, D; Stevenson, L; Prasad, P; Smirnakis, K; Kao, A; Rabah, D; Wang, W; Barbey, C; Musselli, C; Franchimont, N
Abstract : Background: Type I interferons (IFN-I) are central to the pathogenesis of systemic lupus erythematosus (SLE). BDCA2 is a plasmacytoid dendritic cell (pDC)-specific receptor that, upon engagement, inhibits the production of IFN-I and other inflammatory mediators. Targeting BDCA2 therefore represents an attractive therapeutic strategy for inhibiting pDC-derived IFN-I and may be an effective therapy for the treatment of SLE. BIIB059, an investigational anti-BDCA2 humanized monoclonal antibody, has been shown to engage BDCA2, and this interaction leads to BDCA2 internalization and the consequent in vitro inhibition of TLR-induced IFN-I by pDCs (Pellerin 2015). Objectives: This study is a first-in-human study that aimed to assess safety, tolerability, PK and PD of BIIB059 in HV subjects following administration of single ascending doses of BIIB059. Methods: A randomized, double-blinded, placebo controlled, single ascending dose-escalation was conducted in adult HV. Subjects received a single administration of either BIIB059 or placebo. BIIB059 was administered IV at 0.05, 0.3, 1, 3, 10 or 20mg/kg or SC at 50mg at ratio of 2:1 or 3:1. Blood samples were obtained before and after dose administration up to week 16. Target modulation of BDCA2 and serum BDCA2 concentration were measured using flow cytometry, and an enzyme-linked immunosorbent assay (ELISA), respectively, and anti-drug antibodies (ADA) were measured using a bridging ELISA. Results: 54 HV (38 BIIB059; 16 placebo) were assigned to cohort 1–7. BIIB059 demonstrated non-linear PK consistent with target mediated drug disposition. Bioavailability of SC administration was ∼50%. Treatment with BIIB059 led to rapid and complete down-modulation of BDCA2 on the surface of pDCs at all dose levels. Time to reappearance of BDCA2 on pDC cell surface correlated with circulating levels of BIIB059, establishing an in vivo pharmacokinetic/pharmacodynamics (PK/PD) relationship. Single dose administration of BIIB059 was well tolerated across all dose levels. All AEs were mild to moderate in severity with no serious AEs. There were no clinically significant changes in laboratory assessments, physical examinations, or electrocardiogram (ECG) values. Anti-drug antibodies were detected at low levels in a small number of BIIB059-treated subjects. Responses were largely transient and demonstrated no impact on BIIB059 exposure or association with any safety event. Conclusions: The first-in-human study in HV demonstrated acceptable safety/tolerability and PK profile in healthy subjects and supports further multiple-dose studies with BIIB059. BIIB059 treatment showed dose dependent target engagement and internalization of BDCA2 establishing a PK/PD correlation in vivo on circulating pDC. These data support further evaluation of clinical efficacy and safety of BIIB059 as a potential novel therapy in SLE patients. Acknowledgements: None Disclosure of Interest: D. Martin Shareholder of: Biogen, Employee of: Biogen at the time this abstract was written, L. Stevenson Shareholder of: Biogen, Employee of: Biogen, P. Prasad Shareholder of: Biogen, Employee of: Biogen at the time this abstract was written, K. Smirnakis Shareholder of: Biogen, Employee of: Biogen, A. Kao Shareholder of: Biogen, Employee of: Biogen at the time this abstract was written, D. Rabah Shareholder of: Biogen, Employee of: Biogen, W. Wang Shareholder of: Biogen, Employee of: Biogen, C. Barbey Shareholder of: Biogen, Employee of: Biogen, C. Musselli Shareholder of: Biogen, Employee of: Biogen, N. Franchimont Shareholder of: Biogen, Employee of: Biogen